2013
DOI: 10.2478/bvip-2013-0082
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of risk factors associated with infections caused by small ruminant lentiviruses

Abstract: An epidemiological study was conducted to identify risk factors related to small ruminant lentivirus (SRLV) infection in the central region of Spain. Between October 1998 and October 2000, a total of 194 sheep from 10 flocks and 163 goats from three flocks were tested for SRLV antibodies, resulting in 65.5% and 8.0% of seroprevalence, respectively. The relationship between differences in prevalence of SRLV, geographical location of the flock, and possible factors related to the flock that could enhance transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The possibility that inflammation produced by pathologies other than SRLV infection (bacterial infection, traumatism, etc. ) and increased somatic cell counts (SCC) would affect proviral detection has been analysed in other study, where we found no association between PCR results and the SCC or presence of mastitis [26]. A third possibility could be the intermittent shedding of provirus due to seasonal factors, or even to pregnancy and lactation.…”
Section: Discussionmentioning
confidence: 87%
“…The possibility that inflammation produced by pathologies other than SRLV infection (bacterial infection, traumatism, etc. ) and increased somatic cell counts (SCC) would affect proviral detection has been analysed in other study, where we found no association between PCR results and the SCC or presence of mastitis [26]. A third possibility could be the intermittent shedding of provirus due to seasonal factors, or even to pregnancy and lactation.…”
Section: Discussionmentioning
confidence: 87%
“… 1 In addition, there are uncertainties that they are functionally important in vivo, since SRLVs are cell-associated viruses and can spread by cell-to-cell contact, and neutralization may not interfere with viral spread. 1 , 46 Even though the humoral response is not enough to eliminate the viral infection (which is lifelong lasting), some studies have shown that it limits the spread of the viruses. 47 Antibodies do not always help fighting against the infection.…”
Section: The Virus Spreads – and The Body Reactsmentioning
confidence: 99%
“…Exercise intolerance is one of the first clinical signs to be noticed, followed by dyspnea at rest, accompanied by abdominal breathing, neck extension, expansion of the nostrils, and breathing with mouth open. 46 As the disease progresses, the animal suffers from anorexia, weight loss, and finally cachexia. Nasal exudate appears only when there are secondary bacterial infections.…”
Section: The Virus Spreads – and The Body Reactsmentioning
confidence: 99%
See 2 more Smart Citations